PENYULUHAN KESEHATAN TENTANG DBD DAN MALARIA SERTA PEMANFAATAN PELAYANAN FKTP DI RT. 27, KELURAHAN TANJUNG PINANG, KOTA JAMBI - FRANSISKA SITEPU; Rizki Aqsyari (STIKES Garuda Putih, 2025)
Reducing the incidence of dengue fever and malaria is an important indicator of infectious diseases. Maintaining environmental health independently is a key point in reducing the incidence of disease. This community service activity aims to increase public knowledge and understanding of the importance of maintaining environmental health and the facilities provided by the Primary Health Care Facility (FKTP) to support the reduction of dengue fever and malaria incidence. The outreach was carried out through a lecture method and was held in RT. 27, Tanjung Pinang Village, East Jambi District, Jambi City, with 35 participants. The media used was a leaflet. The results of the activity showed an increase in public understanding of dengue fever and malaria. This outreach activity is an important step in reducing the incidence of dengue fever and malaria. Through this activity, the community could increase their knowledge and understanding of dengue fever and malaria so that they are able to maintain environmental cleanliness independently by utilizing the facilities provided by the FKTP.